VARIASI KONSENTRASI PUPUK ORGANIK CAIR (POC) DAN RENTANG WAKTU PENYIRAMAN PUPUK TERHADAP PERTUMBUHAN TANAMAN PAKCOY (Brassica rapa. L) - Ibrahim, Mukhamad Ilham; Daru, Diky Brilian; Hudha, Mohammad Istnaeny (jurnal ATMOSPHERE, 2023)
Liquid organic fertilizer (POC) is the result of a fermentation process of organic materials containing the elements N, P and K. The use of POC has a significant impact on plant growth including plant height, leaf width, plant weight. In this study using fertilizer concentrations of 0, 4, 8, and 12% POC to 1L of water, and fertilization time ranges of 3, 4, 5, and 6 days. From the research that has been done it can be concluded that the best variable is with a concentration of 8%. fertilization every 4 days obtained the value on the 28th day the plant height was 26 cm, the number of leaves was 14, the stem circumference was 25.8 cm, the net weight was 52 grams, but the growth in leaf width was on the 28th day with a concentration of 4% with fertilization every 4 days the optimal value is 14 cm.